Адаптивные системы обработки сигналов РЛС вертикального зондирования атмосферы - Литвин-Попович, А. И.; Олейников, В. Н. (ХНУРЭ, 2008)
Radar wind profilers are used widely for atmospheric state monitoring for means of an air transport meteorological support, ecological monitoring, and atmospheric physics studying. These systems used electromagnetic wave scattering on nonhomogenities of dielectric permeability. In comparison with target-detection radars, wind profilers are used to work with a lot weaker signals that cause some special aspects in the signal processing systems used there.
Keywords: РЛС; зондирование атмосферы